Integrative morphological and phylogenetic analyses reveal Russula subrubricolor (Russulaceae, Russulales), a new ectomycorrhizal fungus from Pakistan - Sana; Kiran, Munazza; Basit, Abdul; Humza, Muhammad; Khan, Muhammad Binyamin; Ali, Wajid (Phytotaxa, 2025)
Ectomycorrhizal fungi are key components of forest ecosystems, and thus, documenting their taxonomic diversity is essential for understanding and maintaining ecosystem stability. The current study deals with the discovery of an ectomycorrhizal species, Russula subrubricolor sp. nov., from Pakistan, based on light microscopy, scanning electron microscopy, and nrITS-based phylogenetic analysis. Phylogenetically, Russula subrubricolor formed a distinct and strongly supported clade (BS=99/PP=1.00) sister to Russula rubricolor, differing by 16 nucleotide substitutions and 15 indels in the nrITS region. The new species is characterized by a brighter red pileus with decurved margins, bright yellow lamellae, a stipe developing yellow coloration at the broader base, globose to subglobose and non-reticulated basidiospores (mean 6.0 × 5.6 µm) consisting of isolated to fused warts, fusiform to narrowly cylindrical hymenial cystidia, and subfusiform pileocystidia. Morphological descriptions, field photos, micrographs, and nrITS-based phylogenetic analyses are presented in this article for the newly described species. This study contributes to the expanding knowledge of Russula diversity in the Himalayan region and highlights the importance of continued mycological exploration in understudied ectomycorrhizal habitats.